Alcohol Related Cerebellar Degeneration: A Case Report - Sharma, Aprajita; Karki, Manoj; Devkota, Sudhan; Mane, Sanket; Lamsal, Samrakchan; Kharel, Samwad (Journal of Universal College of Medical Sciences, 2024)
Alcohol related cerebellar degeneration in one of the feared complications with unsatisfactory recovery that requires high index of suspicion for identiﬁcation. We report a case of 62 years alcohol consumer female who presented with ataxia and dysarthria of subacute onset. She demonstrated bilateral cerebellar signs on examination with MRI brain suggestive of bilateral cerebellar atrophy.